ANALYSIS THE ROLE OF ENTREPRENEURIAL CHARACTERISTIC ON NETWORKING TOWARD SME’S IN MANADO - Tjandrawati, Angela; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2020)
Abstract: The Role of Small and Medium Enterprises (SMEs) in the economy of Indonesia is very significant. It is obvious in Indonesian economy development, this sector carries a big role in the economic growth and national GDP, creating job employment, also play a powerful role during the economic crisis. The role of SMEs in the last few decades is considered strategic, but its performance is not considered maximal in the face of competition and growth of production as a whole in a country. To analyze the Role of Entrepreneurial Characteristic on Networking toward SME’s in Manado. This research is a qualitative research methodology which is descriptive research. Qualitative research usually does use some form of quantification, but statistical forms of analysis are not seen as central. The population of this research is the owners of SME’s in Manado. Based on the result and analysis, the conclusion given in this research is as follows are most of the respondents share with their closest friends to get feedback for their business most of the respondent uses those feedback as a way to improve their business in many aspects. Keywords: entrepreneurial characteristic, entrepreneurial networking